Prognostic impact of small size sutureless prostheses: results for 241 patients from an international registry - Giuseppe Santarpino; Roberto Lorusso; Giovanni Concistrè; Josè Cuenca Castillo; Vincenzo Argano; Alistair Royse; Angelo Lucas Nobre; Patrick Parrino; Gianluigi Bisleri; Max Baghai; Theodor Fischlein; Giovanni Troise; et al. (Journal of Cardiothoracic Surgery)
Abstract Background The treatment of aortic valve disease in small annuli remains a debated topic in terms of prosthetic choice - biological or mechanical - and risk of patient prosthesis mismatch. Methods The clinical data of the 241 patients who received a small size sutureless prosthesis from the Sorin Universal REgistry on Aortic Valve Replacement (SURE-AVR) (NCT02679404) were analysed at 30 days and at follow-up. The mean age was 75.5 ± 7.8 years (89.2% female); the mean Society of Thoracic Surgeons (STS) score was 4.2 ± 3.2%, and the preoperative NYHA class II or III score was 83.8%. A minimally invasive approach was performed in 52.7% of patients; concomitant procedures were performed in 27.8% of patients. Similar aortic clamping and cardiopulmonary bypass times were observed in the overall isolated cohort and the isolated minimally invasive cohort. The mean intensive care unit (ICU) stay was 2.4 ± 2.0 days and the total length of stay was 10.3 ± 6.1 days. Results Three deaths were recorded at 30 days (1.2%), 2 for noncardiac causes. One patient experienced a myocardial infarction (0.4%) and 2 a nondisabling stroke (0.8%). 2 patients showed intraprosthetic leakage ≥ 2 and one patient para-prosthetic leakage ≥ 2; of these, one patient required reoperation with prosthesis removal. 4.1% of patients required a pacemaker implant. At a maximum follow-up of 8.1 years, 10 cardiovascular deaths, 4 valve related reinterventions (3 structural valve deterioration (SVD) requiring TAVI Valve-in-Valve, 1 endocarditis) occurred. Conclusions With their good clinical outcomes, sutureless prostheses represent a good alternative for patients with small annuli, who are at high risk for annular enlargement and anticoagulant therapy. Trial registration Study number 587/2015.